2019
DOI: 10.3329/bjn.v35i1.57627
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Autonomic & Electrophysiological Features in Patients with Guillain Barre Syndrome in a Tertiary Care Hospital of Bangladesh

Abstract: Background: Guillain-Barre Syndrome (GBS) is the most common cause of acute flaccid paralysis in the adult population. It is an acute post infectious immune mediated peripheral neuropathy with a marked variation in pathology, clinical presentation and prognosis. Objective: The aim of the study were to evaluate clinical profile, to assess autonomic involvement & electrophysiological findings in adult patients with GBS. Methods: An observational, cross sectional study was carried out in the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…De-Quervain's Tenosynovitis was discovered in 75% of the tailors out of 100 (13). Another study by N. Jannat et al that employed the franklein test to examine the prevalence of de-quervains syndrome among barbers and tailors reported that De-Quervain's tenosynovitis had been present in 80% of the study population (9). In present research, the study population was carpenters and the reported cases of De-Quervain's Tenosynovitis were much less than the tailors and barbers.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…De-Quervain's Tenosynovitis was discovered in 75% of the tailors out of 100 (13). Another study by N. Jannat et al that employed the franklein test to examine the prevalence of de-quervains syndrome among barbers and tailors reported that De-Quervain's tenosynovitis had been present in 80% of the study population (9). In present research, the study population was carpenters and the reported cases of De-Quervain's Tenosynovitis were much less than the tailors and barbers.…”
Section: Discussionmentioning
confidence: 44%
“…Musculoskeletal disorders (MSDs) are among the most frequent workplace health concerns. It is well documented that ergonomic risk factors such as repetition, Work-related musculoskeletal illnesses (WMSDs) are caused by poor posture and unacceptable levels of contact stress and force (WMSDs) (9). M. Ramdan et al undertook a cross-sectional study in 2022 on 60 motorcycle repair technicians in the Indonesian city of Samarinda with the goal of identifying De Quervain's disease (DQD) prevalence and risk variables.…”
Section: Introductionmentioning
confidence: 99%